Implementation of the Cooperative Learning Model Type STAD (Student Team Achievement Division) to Improve Learning Outcomes in Islamic Religious Education and Character Education - Anis Putri Debi Anggraini; Ahmad Dhiyaa Ul Haqq; Noor Akhmarisha Binti Sa’ari; Nanda Eska Anugrah Nasution (Fakultas Tarbiyah Ilmu Keguruan Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
Islamic Religious Education plays a crucial role in shaping Indonesian students into knowledgeable and morally upright individuals. However, many students struggle with its concepts, leading to poor academic performance. To address this, the study explores the implementation of the Student Team Achievement Division (STAD) cooperative learning model. STAD promotes collaboration in small, diverse teams, encouraging active participation and problem-solving. This research was conducted as a Classroom Action Research (CAR) study at SMP Negeri 2 Mayang Jember with seventh-grade students as participants. The study was carried out in two cycles, each comprising planning, implementation, observation, and reflection. The findings indicated a significant improvement in student learning outcomes after the application of STAD. The average student scores increased from 60 in the pre-test to 70 in the first cycle and further to 80 in the second cycle. The percentage of students achieving the minimum competency criteria rose from 11% in the pre-test to 75% by the end of the second cycle. These results suggest that the STAD model is an effective pedagogical approach for enhancing student learning outcomes in Islamic Religious Education. By creating an engaging and collaborative learning environment, STAD facilitates deeper understanding, promotes active participation, and fosters positive student interactions. Further research is recommended to explore its long-term impact and applicability to different subjects and educational levels.